Pengaruh Penerapan Good Corporate Governance (Gcg) Terhadap Nilai Perusahaan Dengan Kualitas Laba Sebagai Variabel Intervening - Haryanto, Ruli Eko; Komalasari, Agrianti; Lukman, iing (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2024)
This research aims to determine the effect of corporate governance on company value with earnings quality as an intervening variable. The corporate governance mechanism uses three variables, namely the board of commissioners, board of directors, and sharia supervisory board. The research used a sample of 11 sharia banks in 2012-2017. The research method is Multiple Linear Regression Analysis. The results show that the board of commissioners, board of directors, and earnings quality as measured by TACC (Total Accrual) have a negative effect on company value. Meanwhile, the sharia supervisory board has a positive effect on company value, but not significantly. The board of directors has a negative effect on earnings quality. The board of commissioners has a significant positive effect on earnings quality. Meanwhile, the sharia supervisory board has a positive effect on earnings quality, but not significantly. Furthermore, the influence of GCG mechanisms on company value with earnings quality as an intervening variable shows positive results but is not significant. The adjusted R2 value for the influence of GCG mechanisms on earnings quality is 0.157 or 15.7%. Meanwhile, the adjusted R2 value for the influence of GCG mechanisms on company value with earnings quality as an intervening variable is 0.035 or 3.5%.